2015
DOI: 10.1002/cbin.10452
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of stem cells under outer‐space microgravity and ground‐based microgravity simulation

Abstract: With rapid development of space engineering, research on life sciences in space is being conducted extensively, especially cellular and molecular studies on space medicine. Stem cells, undifferentiated cells that can differentiate into specialized cells, are considered a key resource for regenerative medicine. Research on stem cells under conditions of microgravity during a space flight or a ground-based simulation has generated several excellent findings. To help readers understand the effects of outer space … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…In particular, cells seemed to have partially lost their typical spindle-like shape presenting a flattened form (white arrows, Figures 2D,F ). This effect is in line with previous studied carried out on stem cells in MG morphology ( Zhu et al, 2014 ; Zhang et al, 2015 ; Xue et al, 2017 ).…”
Section: Resultssupporting
confidence: 92%
“…In particular, cells seemed to have partially lost their typical spindle-like shape presenting a flattened form (white arrows, Figures 2D,F ). This effect is in line with previous studied carried out on stem cells in MG morphology ( Zhu et al, 2014 ; Zhang et al, 2015 ; Xue et al, 2017 ).…”
Section: Resultssupporting
confidence: 92%
“…To some extent, MG cells resemble neural stem cells [6], which have been studied in space conditions by other groups. Murine neural stem cells, cultivated in a 3D bioreactor in space, maintained their ''stemness,'' even displayed upregulation of stem cell transcription factors Sox2 and Pax6, but proliferated slower than in 1 g and underwent neural differentiation more readily [15].…”
Section: Müller Gliamentioning
confidence: 99%
“…Research in this area utilizes a wide range of cell models, most common being cultured human or rodent stem cells. Taken together, results show the effects of real and simulated microgravity on stem cell migration, proliferation, and differentiation-key processes in tissue development and regeneration [1][2][3][4][5][6][7]. Original hardware is being developed to conduct such experiments onboard spacecrafts and in laboratories, and new ways of utilizing methods of cell culture in microgravity, as well as cells themselves, in bioengineering and regenerative medicine are being proposed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have demonstrated that the conditions in outer space promote neuronal differentiation of NSCs [9]. As microgravity is one of the key factors of outer space [10,11], this present study investigated the influence of simulated microgravity on three-dimensional (3D) cultured NSCs with a dynamic 3D Rotary Cell Culture System (RCCS). The microgravity environment within the RCCS bioreactor is provided by using a random positioning machine that produces low fluid shear force.…”
Section: Introductionmentioning
confidence: 99%